A Novel miRNA—hlo-miR-2—Serves as a Regulatory Factor That Controls Molting Events by Targeting CPR1 in Haemaphysalis longicornis Nymphs - Liu, Wen-Ge; Luo, Jin; Ren, Qiao-Yun; Qu, Zhi-Qiang; Lin, Han-Liang; Xu, Xiao-Feng; Ni, Jun; Xiao, Rong-Hai; Chen, Rong-Gui; Rashid, Muhammad; Wu, Ze-Gong; Tan, Yang-Chun; et al. (Frontiers in Microbiology, 2020)
Successful completion of the molting process requires new epidermal growth and ecdysis of the old cuticle in Haemaphysalis longicornis (H. longicornis). MicroRNAs (miRNAs) participate in the development of organisms by inhibiting the expression of their target mRNAs. In this study, we identified a novel tick-specific miRNA denoted hlo-miR-2 that serves as a novel regulator of molting events in H. longicornis nymphs by targeting a cuticular protein. We first obtained the full length of this cuticular protein and named it CPR1. A qRT-PCR analysis showed that hlo-miR-2 and CPR1 exhibit significant tissue and temporal specificity and that their transcription levels are negatively correlated during the molting process. CPR1, as a direct target of hlo-miR-2, was identified by a luciferase reporter assay in vitro. Agomir treatment indicated that the overexpression of hlo-miR-2 significantly reduced the protein expression level of CPR1, decreased the molting rate and delayed the molting time point in H. longicornis nymphs. RNA interference (RNAi) experiments demonstrated that CPR1 was significantly associated with the molting process in H. longicornis nymphs. Phenotypic rescue experiments convincingly showed that hlo-miR-2 participated in molting events by targeting CPR1 in H. longicornis nymphs. In summary, we present evidence demonstrating that miRNAs constitute a novel important regulator of molting events in addition to hormones. The described functional evidence implicating a cuticular protein in molting events contributes to an improved understanding of the distinct functions of the CPR family in ticks and will aid the development of a promising application of cuticular protein RNAi in tick control.